Prevalence, genotypes of human papillomavirus infection and risk factors for persistence in a cohort of HIV - Infected Pregnant Women - Meyrelles, Angela Rosa Império (Brazilian Journal of Sexually Transmitted Diseases, 2023)
HIV-positive pregnant women are more vulnerable to infection and persistence of human papillomavirus (HPV). The aim of this study was to determine the prevalence and genotypes of HPV in a cohort of HIV-positive pregnant women during pregnancy and one year after delivery, analyzing risk factors for persistence. A prospective study was performed with pregnant women followed-up in the Integral Assistance Program for HIV-positive Pregnant Women of the Federal University of Rio de Janeiro, between 2009 and 2011. Demographic, clinical and laboratorial data were evaluated. Cervical samples were collected during pregnancy and one year after delivery. HPV DNA and p53 gene were amplified by polymerase chain reaction (PCR) technique and cloning. HPV direct PCR sequences were typed by submission to Blast Search tool at the National Center for Biotechnology Information (NCBI) website. The prevalence of HPV during pregnancy was 84.3% (118/140), and 106 samples were genotyped. Thirty different HPV types were founded, of which 81.1% were high-risk type. The most prevalent types were: 16, 58, 35, and 53. Infection by multiple types occurred in 18.9%. Persistent infection was noted in 50%, being 30% type-specific and 20% reinfection cases. Persistence was correlated with a TCD4+ count ≤ 350 cells/mm³ (p = 0.05). No correlation was observed between p53 polymorphism and infection by HPV or persistence of HPV infection. In conclusion, there was a high rate of HPV prevalence in this cohort of HIV-positive pregnant women, with a predominance of oncogenic types and persistence of infection in half of the cases, which was correlated with immune suppression.